What Do You Learn About Hard News from Soft News Outlets - A Case Study from People Magazine Online - Yan, Jason; Milita, Kerri; Krupnikov, Yanna; Tomkins, Sabina (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
People are increasingly avoiding the news in a phenomenon termed news avoidance. Prior work has found that many people are not following political news, with the median American consuming zero articles per year from traditional news outlets. This behavior has troubling implications, as a well-informed public is typically considered essential to a functioning democracy. However, it is possible that people are accidentally picking up political information through entertainment or "soft news" outlets. The subject of this paper is People Magazine, a soft news outlet selected for its popularity (with an average of 187.1 million monthly visits). To understand how political news is covered by entertainment and soft news outlets, we make the following contributions: (1) we propose two potential and complementary frameworks for differentiating hard news content from soft news content; (2) we collect a large dataset of articles published on People Magazine's website; (3) we apply our frameworks to this dataset and contribute an analysis of the political content offered by a soft news outlet; (4) we evaluate our framework on two additional platforms. Together, these contributions additively result in the first exploration of the political content of individual news stories - all prior work has labeled entire outlets as hard or soft. As people increasingly avoid outlets with hard news, our work shows that they may still encounter political information through soft news outlets, a finding that has critical implications for political communication.